2 Physiological response to adenosine and splenic switch off. (18th May 2017) - Crowther, Oliver; Hamilton, Mark
Abstract : Introduction: Cardiac magnetic resonance perfusion studies require a patient to be 'adequately' physiologically stressed to ensure reliable data. The principle aim of this study was to investigate the assumption that the standard adenosine dose (140mcg/kg/min) achieves this stress. A secondary aim was to investigate splenic switch off (SSO), this has recently been reported as a marker of adequate response to adenosine. Methods: An adequate stress response was defined as >20% increase in heart rate (HR) plus >3/5 symptom discomfort (5-?point scale). Three separate adenosine infusion protocols were trialled, depending on patient physiological responses. Protocol A: 140 mcg/kg/min for 4mins. Protocol B: 140 mcg/kg/min for 2mins then 210mcg/kg/min for 2mins. Protocol C: 140?mcg/kg/min for 2mins then 210?mcg/kg/min for 4mins. After exclusion of studies that were "off-protocol", 67 studies were eligible. Splenic enhancement was assessed using CMR42 (Circle CVI, Calgary, Canada) software, creating regions of interest. Significance (P<0.05) was determined using Two-sample T-tests and ANOVAs. Results: No significant differences were observed between protocols considering HR response, symptom severity or splenic enhancement. 3 distinct splenic responses were revealed. The ten best enhancing spleens were similar to blood pool whilst the ten lowest resembled SSO. These three subgroups of splenic enhancement showed no correlation to HR or symptom response. Conclusions: We would recommend the described adenosine protocol as a consistent way of overcoming poor responses. In terms of SSO, sub group analysis of splenic enhancement shows it is unrelated to HR or symptomatic response, suggesting SSO may not reflect vasodilator stress.